Persepsi dan Dukungan Keluarga terhadap Pemberian Imunisasi Measles Rubella (MR): Perception and Family Support for the Administering of Measles-Rubella (MR) Immunization - Rafidah, Rafidah; Yuliastuti, Erni (Jurnal Bidan Cerdas, 2020)
Nationally, MR immunization is 51.05% as of September 30, 2018. MR immunization coverage in South Kalimantan Province until October 31, 2018, is 56.58%. The lowest achievement is Banjar Regency, with 36.46%. The study aimed to determine the relationship between perception and family support (husband) with MR immunization. The study design used a cross-sectional study. The study population was mothers who had children aged nine months to 15 years in the working area of the Beruntung Baru Public Health Center, totaling 6,379 people. The sample size was 377 people. This study used accidental sampling. Univariate data analysis and bivariate analysis with Chi-Square statistical test. The results of the study showed a relationship between perceptions (p-value=0,001; OR=24,7) and and family support (p-value=0,001; OR=9,3) with giving MR immunization. This study suggests the Beruntung Baru public health center to improve health promotion on MR immunization by holding counseling so that the public could better understand MR immunization.